Understanding the Nature of the Adsorption of Zn(Ii)/Si(Iv) Phthalocyanines on Anatase tio2 and Rutile sno2 - Cardenas-Jiron, G; Zambrano-Angulo, M (Springer Science and Business Media Deutschland GmbH, 2024)
Context: The zinc (II) and silicon (IV) phthalocyanine adsorption on a TiO2 and SnO2 semiconductor surface was investigated using the density functional theory. Several effects were studied: the semiconductor (TiO2, SnO2), the central metal atom in the phthalocyanine (Zn, Si), the substituent groups in the phthalocyanine, and the anchor group (anhydrous, carboxyl) connecting the phthalocyanine with the semiconductor. The application of methodologies to study the intermolecular interactions predicted a stronger zinc and silicon phthalocyanine adsorption with carboxyl than anhydrous. Adsorption energies for phthalocyanines anchored by a carboxyl group indicate a stronger adsorption for TiO2 than for SnO2 with energy differences of up to 7 eV. The presence of coordinative and more van der Waals interactions in TiO2 can explain this. This work is carried out to understand the interaction between phthalocyanines and the semiconductor surface, a crucial aspect of the efficient performance of solar cells. Methods: We modeled two semiconductor surfaces in extended configuration (TiO2 and SnO2), which were optimized with the GGA-PBE exchange–correlation functional for solids, including the Grimme’s correction dispersion (D3). The meta-GGA TB09LDA exchange–correlation functional was employed to calculate the band gap energy of the semiconductors. The adsorption energies of the phthalocyanines adsorbed on the semiconductors were determined with GGA-PBE-D3 and corrected by the counterpoise method. The nature of the intermolecular interactions in the adsorption was analyzed using the non-covalent interactions (NCI) based on the promolecular approximation of electron density. These interactions were quantifiable by employing the intrinsic bond strength index (IBSI). We used the QuantumATK and the Multiwfn packages for all the calculations. © The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature 2024.